Primary uterine non-Hodgkin’s lymphoma:a rare case report and review of the literature - Wu, Jing; Liu, Ting (Frontiers in Oncology, 2024)
Primary uterine non-Hodgkin lymphoma (NHL) is rarely reported, as its incidence is extremely low. We describe a 72 year old patient with primary uterine non-Hodgkin’s lymphoma stage IV, diffuse B-cell large cells, who responded well to cytotoxic chemotherapy (R-CHOP). Radiological investigations exhibited certain characteristics, including magnetic resonance T2 weighted imaging, enhanced scanning, diffusion weighted imaging and apparent diffusion coefficient values. The lesion in the anterior wall of the uterine body was relatively large, with a size of about 34mm×47mm×43mm. The gold standard for diagnosis is still the pathological examination of a biopsy specimen, which revealed diffuse large cell of B lineage. This article reviews data collected from 141 patients in the literature.